Analysis Of Employees' Affective Commitment To Performance Mediated Employee Involvement Of The National Narcotics Agency North Sumatera Province - Megawati; Wilchan Robain (Yayasan Multidimensi Kreatif, 2024)
The aim of this research is to analyze and determine the influence of affective commitment on employee performance in the Provincial BNN work unit and to analyze the influence of affective commitment on employee performance which is mediated by employee involvement in the Provincial BNN work unit. This type of research is quantitative descriptive, the research sample was 56 people, and the data was analyzed using the SEM (structural equation modeling) method. Overall, from the results and discussion in the research, it is concluded that there is a positive and significant influence between affective commitment on employee performance, and the employee involvement variable is unable to mediate affective commitment on employee performance in the North Sumatera Province BNN Work Unit.